THE POSSIBILITIES AND LIMITATIONS OF ENTREPRENEURSHIP DEVELOPMENT IN AGRICULTURE IN SERBIA - Aničić, Jugoslav; Vukotić, Svetlana; Maksimović, Goran (Economics of Agriculture, 2018)
The Republic of Serbia is very convenient for agricultural production: large, high-quality arable land, favourable climate conditions for all agricultural cultures, rich flora and fauna, rich tradition and developed scientifc institutions are the priceless treasure of Serbian agriculture. However, the results of numerous research show that Serbian agriculture competitiveness is based on cheap production factors compared to other countries (soil, workforce, other inputs). One of the ways of solving this situation is larger application of entrepreneurial type of production in agribusiness, for which there are great possibilities in Serbia. This paper analyses the position of agriculture at the moment, and points out the importance and the need for faster and wider development of an entrepreneurial orientation in this sector. Serbia is in the EU accession process, and therefore the imperative of approaching the European model of doing business and the need for companies and family economies in agribusiness to build and protect their competitive advantages. In order to achieve this goal, traditional weaknesses should be overcome, so education and introduction of entrepreneurship into the school system are a good basis for farmers to have a stronger influence on the economic policy carriers as well as the adequate treatment of agricultural sector at the macroeconomic level.